On disease configurations, black-grass blowback, and probiotic pest management - Cusworth, G; Lorimer, J (Taylor and Francis, 2024)
This article explores approaches to managing pests that are being developed in response to the faltering effectiveness of antibiotic regimes of chemical control. It focuses on black-grass (Alopecurus myosuroides), an endemic plant in European agriculture that has emerged as a serious yield-robber with increasing levels of herbicidal resistance. Following farmers and agronomists who have developed “integrated” approaches to black-grass management, the article identifies approaches to biosecurity that do not target unwanted life so much as they modulate ecological systems in their entirety. Pathogenesis, in this relational understanding, follows not from breaches of dangerous life into healthy space, but from ecological intra-actions that enable the proliferation of some life to compromise the multispecies livability of the body in question. The article contributes to the literature by detailing how this configurational approach works in the world. It traces the polymorphic spatial imaginaries required to map pests well; the process of knowledge intensification needed to reveal which configurations can resist pathogenesis; and the probiotic biopolitical interventions used to safeguard farmland productivity. The article uses black-grass to present a temporal metanarrative of intensive farming causing ecological blowback, leading to the development of approaches to pest management predicated on a pragmatic tolerance toward unwanted life.